2015
DOI: 10.1109/ted.2014.2372819
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Superjunction Structure With Variation Vertical Doping Profile

Abstract: An analysis of an improved superjunction structure with variation vertical doping profile (VVD-SJ) is presented in this brief. It features a better tradeoff between breakdown voltage (BV) and specific ON-resistance (R on ) than the prior art, due to a higher average doping concentration in columns. A simple 2-D electric field model of the VVD-SJ structure is derived based on charge superposition principle. Optimized results show that the specific ON-resistance of the VVD-SJ structure is reduced by ∼10%, compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 9 publications
1
18
0
Order By: Relevance
“…This improvement is due to increment in average doping concentration of n-column. 13,14 Eventually, the current driving capacity of the proposed structure is enhanced. Figure 5A exhibits output characteristics for k = 5, Figure 5B shows output characteristics for k = 10, and Figure 5C represents output characteristics for k = 20.…”
Section: Electrical Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…This improvement is due to increment in average doping concentration of n-column. 13,14 Eventually, the current driving capacity of the proposed structure is enhanced. Figure 5A exhibits output characteristics for k = 5, Figure 5B shows output characteristics for k = 10, and Figure 5C represents output characteristics for k = 20.…”
Section: Electrical Characteristicsmentioning
confidence: 99%
“…They suggested that nonuniform doping leads to the reduction of area specific on-resistance. 13,14 Abbreviations: ANA, antinuclear antibodies; APC, antigen-presenting cells; IRF, interferon regulatory factor.…”
mentioning
confidence: 99%
“…The R SP determines the power dissipation of the device, but it is difficult to realize a low R SP for the determined BV due to the one-dimensional silicon limit. Super-junction (SJ) structures [1][2][3][4] in the drift region have been proposed in order to overcome it. The SJ can decrease the R SP effectively at a given BV.…”
Section: Introductionmentioning
confidence: 99%
“…Injection efficiency controlled IGBTs (IEC-IGBT) have been shown to be effective in the trade-off between V on and E off [8]- [12]. Other published structures such as reverse-conducting IGBT [13], snapback-free reverse-conducting IGBT [14], IGBT with pinched-off ntype pillar [15], SJ-IGBT [16]- [20], CSTBT [21], [22] and IGBT with Controllable Trench Gate [23] etc., are also favorable for enhancing the trade-off between V on and E off . For future IGBTs, it will be more and more important to consider the trade-off between switching and on-state losses based on novel device structures and advanced manufacturing techniques [24].…”
Section: Introductionmentioning
confidence: 99%